Students’ essay writing anxiety: A narrative study of Indonesian tertiary EFL learners - Faismaul Ro’ufiyati, Dinda; Mahbub, Moh. Arif (JEES (Journal of English Educators Society), 2023)
Recent years, numerous studies across the world have examined EFL learners’ writing anxiety through their writing test. Yet, there is limited study on investigating learners’ anxiety in essay writing, particularly contextualized in Indonesia. Viewed from the lens of narrative study, this article explores the lived-experience of the university students’ essay writing anxiety situated in a private university in the eastern Java, Indonesia. Two students enrolled in “Critical Essay Writing” Course (KBI112) volunteered to be involved in the study. Grounded in the thematic analysis (Braun & Clarke, 2006) as an analytic lens, findings indicate that the major factors significantly contribute to learners’ essay writing anxiety include: low level writing skill and confidence; learners’ self-efficacy; self-esteem; lack of grammatical knowledge; gender; instructor’s negative feedback; and writing motivation level. Empirical data also reveals that the students with higher writing anxiety level tend to produce low quality writing products and vice versa. This empirical evidence suggests that both teachers and students are highly required to intensify their efforts to create positive learning environment that can make the students to manage their feelings so that they can produce the better quality of essay writing products. This article also discusses pedagogical implications for classrooms and further research, limitations and recommendations. HIGHLIGHTS: Learners' writing anxiety was significantly affected by both internal and external factors. Learners with higher level of anxiety tend to produce lower writibg performamce. Managing learners' emotional feelings is a must-do action to reduce their writing anxiety.